Can invitation systems increase participation in preventive health screening among adolescents?: An evaluation of a state-wide intervention in Germany using a difference-in-differences analysis of claims data - Iashchenko, Iryna; Schüttig, Wiebke; Bammert, Philip; Schneider, Udo; Spallek, Jacob; Rattay, Petra; Schneider, Sven; Moor, Irene; Pischke, Claudia Ruth; Sundmacher, Leonie (European journal of public health, 2025)
In Germany, routine screenings are used to monitor the health and development of children and adolescents, enabling timely discovery and treatment of health issues. One such screening, called J1, is recommended for adolescents aged 12-14 years, but participation is only 43%. In the state of Bavaria, a lack of awareness is the main reason cited for not attending. ‘Your Ticket to J1’ was an invitation system implemented across the state to inform adolescents about the screening. Our study investigated whether this intervention increased J1 participation and if its effects varied by family socioeconomic position (SEP). We used pseudonymized data from a large statutory health insurer from 2016 to 2018 and containing 267 650 observations. To investigate the effect of the intervention, we employed a difference-in-differences analysis at the individual level. Assuming parallel trends at the state level, we compared J1 participation rates between Bavaria and other German states before and after the intervention. We additionally stratified analyses by SEP. The intervention led to an increase in J1 participation by about 1%. In the stratified regressions, the effect size was larger for children from families with a lower SEP. J1 participation increased by about 4% among adolescents whose primary insured parent had the lowest occupational status. A state-wide invitation system had a small but statistically significant positive impact on J1 participation and might reduce socioeconomic inequities in healthcare utilization. Informing adolescents about J1 appears to increase participation, particularly among those from families with a lower SEP.